Composition‐induced non‐ergodic–ergodic transition and electrocaloric evolution in Pb1−1.5x Lax Zr0.8 Ti0.2 O3 relaxor ferroelectric ceramics. Issue 4 (30th October 2019) - Li, Junjie; Yin, Ruowei; Su, Xiaopo; Li, Jianting; Qin, Shiqiang; Wei, Qiumei; Zhu, Mankang; Guo, Dong; Qiao, Lijie; Bai, Yang
Abstract : Relaxor ferroelectrics, with polar nanoregions (PNRs), are good candidates for electrocaloric (EC) refrigeration. This study investigates the EC performance of the Pb1−1.5 x La x Zr0.8 Ti0.2 O3 relaxor ferroelectric ceramics by the direct measurement using a modified differential scanning calorimeter. All the ceramics exhibit pure perovskite phase with a dense microstructure. The results indicate that the increasing La substitution strengthens the relaxor behaviour, promotes the transition from non‐ergodic to ergodic state, and enhances the thermal stability of EC property (instability η  < 16% within 0–140°C for x  = 0.09). While the EC peak widens and shifts to lower temperatures, the peak value decreases from Δ T max  = 0.98 K (@140°C) for x  = 0.06 to Δ T max  = 0.25 K (@40°C) for x  = 0.09 under an electric field of 40 kV/cm. Moreover, the ceramics with x  = 0.07, near the non‐ergodic–ergodic state boundary, show the optimised room temperature EC performance, i.e. Δ T  = 0.41 K (@20°C) and η  < 20% within a wide temperature range of 0–80°C. This work provides an effective material design approach for EC refrigeration in different application conditions.